Interleukin 17 Receptor Gene Polymorphism in Periimplantitis and Chronic Periodontitis - Mahdi Kadkhodazadeh; Ahmad Reza Ebadian; Reza Amid; Navid Youssefi; Amir Reza Mehdizadeh (Acta Medica Iranica, 2013)
Gene polymorphism of cytokines influencing their function has been known as a contributing factor in the pathogenesis of inflammatory diseases of the tooth and implant supporting tissues. The aim of this study was to investigate the association of IL-17R gene polymorphism (rs879576) with chronic periodontitis and periimplantitis in an Iranian population. 73 patients with chronic periodontitis, 37 patients with periimplantitis and 83 periodontally healthy patients were enrolled in this study. 5cc blood was obtained from each subject's arm vein and transferred to tubes containing EDTA. Genomic DNA was extracted using Miller's Salting Out technique. The DNA was transferred into 96 division plates, transported to Kbioscience Institute in United Kingdom and analyzed using the Kbioscience Competitive Allele Specific PCR (KASP) technique. Chi-square and Kruskal Wallis tests were used to analyze differences in the expression of genotypes and frequency of alleles in disease and control groups (P-Value less than 0.05 was considered statistically significant). There were no significant differences between periodontitis, periimplantitis with AA, GG, GA genotype of IL-17R gene (P=0.8239). Also comparison of frequency of alleles in SNP rs879576 of IL-17R gene between the chronic periodontitis group and periimplantitis group did not revealed statistically significant differences (P=0.8239). The enigma of IL-17 and its polymorphism-role in periodontitis and periimplantitis is yet to be investigated more carefully throughout further research but this article demonstrates that polymorphism of IL-17R plays no significant role in incidence of chronic periodontitis and Periimplantitis.